2017
DOI: 10.3892/etm.2017.4749
|View full text |Cite
|
Sign up to set email alerts
|

Triptolide inhibits the function of TNF-α in osteoblast differentiation by inhibiting the NF-κB signaling pathway

Abstract: Abstract. Chronic inflammation often delays fracture healing or leads to bone nonunion. Effectively suppressing pathological inflammation is crucial for fracture healing or bone remodeling. Triptolide, which is a diterpenoid epoxide, is the major active component of the Thunder God Vine, Tripterygium wilfordii. The aim of the present study was to investigate the role of triptolide in osteoblast differentiation and explore the molecular mechanisms of triptolide in fracture healing. Alkaline phosphatase (ALP) ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 39 publications
1
11
0
Order By: Relevance
“…An in vitro study demonstrated the suppressive effect of triptolide on osteoblast proliferation and mineralization 35. Nevertheless, in another in vitro study, triptolide was found to be able to reverse TNF-α-associated suppression of osteoblast differentiation 36. The process of bone formation plays an important role in OTM, which could sustain the structural integrity of alveolar bone.…”
Section: Discussionmentioning
confidence: 99%
“…An in vitro study demonstrated the suppressive effect of triptolide on osteoblast proliferation and mineralization 35. Nevertheless, in another in vitro study, triptolide was found to be able to reverse TNF-α-associated suppression of osteoblast differentiation 36. The process of bone formation plays an important role in OTM, which could sustain the structural integrity of alveolar bone.…”
Section: Discussionmentioning
confidence: 99%
“…These results suggested that the regulation of Rad gene expression levels in nonunions is associated with TNF-α but not with PDGF. Chronic inflammation, which involves potent pro-inflammatory cytokines such as TNF-α, is well known as a factor that can lead to the development of nonunion [30]. High concentrations of TNF-α have been reported to inhibit osteoblast differentiation [31], and one of the mechanisms is thought to be the downregulation of preosteoblast epidermal growth factor-like repeat protein by meprin, A5 protein, and receptor protein-tyrosine phosphatase l domain (POEM) [32].…”
Section: Discussionmentioning
confidence: 99%
“…Research by Xu et al indicated that TP could enhance the expression of IL-10 and TGF-β1 secreted by Tregs in vitro, which further inhibit osteoclast formation and bone resorption [ 6 ]. In another study, TP was found be able to reverse TNF-α-associated suppression of osteoblast differentiation, suggesting that TP might have a positive effect on bone remodeling [ 56 ].…”
Section: Effect and Mechanisms Of Triptolide (Tp) In Rheumatoid Armentioning
confidence: 99%